Perception of biodiversity: what is the contribution of basic education? (Research, Society and Development, 2022)
Biodiversity is commonly referred to as the biological diversity and variety of life forms, but these organisms should not be observed individually, but rather as a complex and functional structure that interacts with each other. Educating citizens from an early age to know the biodiversity of their region and then helping to conserve, preserve and protect it is a very important process. Our objective was to analyze the knowledge of students in the last year of high school on the topic of regional biodiversity. It is a qualitative and quantitative research, carried out in three schools, in three different municipalities, with 65 students. Among the three levels of biodiversity, students know the diversity of species. Most of them conceptualize native and endemic species, but do not know how to conceptualize exotic species. In general, they understand that the great importance of biodiversity is ecological balance and that the loss of biodiversity will lead to ecological imbalance. Native species, cited more frequently, are species present in urban areas and students with more contact with nature cite, on average, a greater number of species, indicating the importance of rescuing contact with nature.